2023
DOI: 10.1158/0008-5472.c.6512334.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Intratumoral Copper Modulates PD-L1 Expression and Influences Tumor Immune Evasion

Abstract: <div>Abstract<p>Therapeutic checkpoint antibodies blocking programmed death receptor 1/programmed death ligand 1 (PD-L1) signaling have radically improved clinical outcomes in cancer. However, the regulation of PD-L1 expression on tumor cells is still poorly understood. Here we show that intratumoral copper levels influence PD-L1 expression in cancer cells. Deep analysis of the The Cancer Genome Atlas database and tissue microarrays showed strong correlation between the major copper influx transpor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A nomogram was then created to facilitate clinical application, incorporating clinical features to provide a customized scoring system for physicians. A previous study showed that copper regulates key signaling pathways that underlie PD-L1-mediated immune evasion in cancer; reducing copper levels in tumor cells with copper chelators increases CD8 + T cells and inhibits cancer progression (Voli et al, 2020). Thus, we hypothesized that copper metabolism shuts down antitumor immunity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A nomogram was then created to facilitate clinical application, incorporating clinical features to provide a customized scoring system for physicians. A previous study showed that copper regulates key signaling pathways that underlie PD-L1-mediated immune evasion in cancer; reducing copper levels in tumor cells with copper chelators increases CD8 + T cells and inhibits cancer progression (Voli et al, 2020). Thus, we hypothesized that copper metabolism shuts down antitumor immunity.…”
Section: Discussionmentioning
confidence: 93%
“…(Kim et al, 2008). Recently, copper has been shown to regulate the expression of programmed death ligand 1 (PDL1), a transmembrane protein regulated on the surface of some cancer cells that allows immune evasion (Voli et al, 2020). Furthermore, the anti-tumor effects of the immune response depend on effective mitochondrial function, and copper deficiency inhibits the immune response (Shanbhag et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, copper impacts PD-L1, an immune checkpoint inhibitor implicated in cancer immune evasion. Studies have highlighted that depleting copper facilitates the degradation of PD-L1, inhibiting tumor growth and enhancing survival rates in animal models (Voli et al, 2020).…”
Section: Coppermentioning
confidence: 99%
“…Similarly, artificially overexpressing copper importer SLC31A1 resulted in Cu over-accumulation, thereby triggered cuproptosis in A549 lung cancer cells (Tsvetkov et al, 2022). Whereas, depleting cupric ion with copper chelators reduced PD-L1 expression by both inhibiting PD-L1 transcription and promoting PD-L1 ubiquitination degradation in xenograft mouse (Voli et al, 2020). The evidence suggested that cuproptosis was tightly associated with tumor progression.…”
Section: Introductionmentioning
confidence: 97%